1993
DOI: 10.1017/s0924933800005459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tianeptine on attention, memory and psychomotor performances using neuropsychological methods in young healthy volunteers

Abstract: SummaryA study was performed in young healthy volunteers in order to test the possible action of tianeptine, a new antidepressant drug, on cognitive performances. Attention tests, memory tests, a non-verbal inductive reasoning test and a sleep questionnaire were used in this double-blind placebo-controlled crossover study. The two one-week drug administration periods were separated by a one-week wash-out period. The methodology permitted us to evaluate the learning effect during the familiarization with the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…54 Moreover, a study in young HCs found no effect on EEG sleep parameters at therapeutic dosages (37.5 mg/day). 55 The same study found improvement in sleep with tianeptine using the subjective Leeds sleep evaluation questionnaire.…”
Section: Effects Of Antidepressant Drugs On Sleepmentioning
confidence: 87%
“…54 Moreover, a study in young HCs found no effect on EEG sleep parameters at therapeutic dosages (37.5 mg/day). 55 The same study found improvement in sleep with tianeptine using the subjective Leeds sleep evaluation questionnaire.…”
Section: Effects Of Antidepressant Drugs On Sleepmentioning
confidence: 87%